Pengaruh Price Discount, E-Trust, and E-Satisfaction Terhadap Repurchase Intention pada Pelanggan Marketplace Shopee : Studi Pada Mahasiswa Program Studi Diploma IV Manajemen Pemasaran Tahun Angkatan 2019 – 2020 Politeknik Negeri Malang - Laila Maghfiroh; Baroroh Lestari (Jurnal Kewirausahaan Cerdas dan Digital, 2025)
The rapid development of information and technology brings changes in many fields. One of them is in the field of trading which is now carried out online through marketplace. Price discount, E-Trust, and E-Satisfaction are three aspects that play an important role in online business. Therefore, this research was conducted to understand and analyze the impact of Price Discount, E-Trust, and E-Satisfaction on Repurchase Intention in Shopee Marketplace among the students of DIV Marketing Management Study Program class of 2019-2020. This research was a quantitative research. There were three measurements used in this research, namely Price Discount, E-Trust, and E-Satisfaction with Repurchase Intention. The sample obtained by applying nonprobability sampling technique with purposive sampling approach. In analyzing the data, the researcher used descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination, and hypothesis testing. The result of data analysis shows that, there is an impact between Price Discount, E-Trust, and E-Satisfaction with Repurchase Intention on the customers of Shopee marketplace partially or simultaneously. In conclusion, to increase Shopee customers’ loyalty, the marketplace must be aware that price discount, trust, and satisfaction of customers become the most important aspects that determine the marketplace's success.